The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ejoc.201300480
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Catalytic Amination of Phenothiazine; Reliable Access to Phenothiazine Analogues of Tröger's Base

Abstract: Efficient protocols for microwave‐assisted catalyzed amination of halogeno‐phenothiazines are described. Phenothiazine analogues of Tröger's base (PTB) were obtained by condensation of amino‐phenothiazines with formaldehyde in HCl/EtOH/H2O and structurally characterized by NMR and XRD analyses. The formation of PTB isomers was predicted by computational analysis based on theoretical methods (DFT and HF). Electronic properties of the parent amino‐phenothiazines and PTB were assessed on the basis of cyclic volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Cyclic voltammetry (CV) was carried out in dichloromethane, with ferrocene/ferrocenium (Fc/Fc + ) as the internal standard, scanning in the anodic (up to 1.8 V) and cathodic (up to −0.2 V) region. In the case of compounds 3 and 4, the first oxidation potential is due to the phenothiazine moiety 19 and is quasireversible for both compounds, while the second oxidation potential for compound 3 (1.109 V) and the second and third oxidation potentials (1.112 V and 1.446 V, respectively) for compound 4 are generated by phosphorus oxidation and the processes are irreversible (ESI, Fig. S2 †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic voltammetry (CV) was carried out in dichloromethane, with ferrocene/ferrocenium (Fc/Fc + ) as the internal standard, scanning in the anodic (up to 1.8 V) and cathodic (up to −0.2 V) region. In the case of compounds 3 and 4, the first oxidation potential is due to the phenothiazine moiety 19 and is quasireversible for both compounds, while the second oxidation potential for compound 3 (1.109 V) and the second and third oxidation potentials (1.112 V and 1.446 V, respectively) for compound 4 are generated by phosphorus oxidation and the processes are irreversible (ESI, Fig. S2 †).…”
Section: Resultsmentioning
confidence: 99%
“…For the highest tested concentrations of all three compounds, the disappearance of some relaxed form of DNA and an agglomeration of DNA molecules that did not migrate and remained in the wells was observed, similar to other phenothiazine-containing compounds, such as 2-amino-10-methyl-10H-phenothiazine and a phenothiazine analogue of Tröger's base. 19 The Pd II and Pt II complexes of 4-PPh 2 -substituted phenothiazine 4 are capable of binding DNA to generate molecular aggregates with different migration capacities in the electrophoresis experiment compared to the free DNA.…”
Section: Interactions With Dnamentioning
confidence: 99%
“…The starting N -(phenothiazin-3-yl)-amides 1a – e , were prepared from 3-amino-PTZ precursor (conveniently accessible according to our reported microwaves assisted amination procedure [ 29 ]) by acylation with different acyl chlorides. The N -(phenothiazine-3-yl)-thioamides 2a – e were synthesized in variable yields using Lawesson’s reagent for the conversion of amide functional group into its thio-analogue.…”
Section: Resultsmentioning
confidence: 99%
“…The authors have concluded that the reaction proceed smoothly using a catalytic amount (2.5 mol %) of Cu(OTf) 2 in AcOH/H 2 O as a solvent, and the resulting mixture was then heated in a microwave oven at 110 • C for 2-15 min producing substituted acetophenones in low to excellent yields, Scheme 75. In another study, Silaghi-Dumitrescu and coworkers have synthesized aminophenothiazine derivatives under microwave-assisted amination procedure [136]. Various hallo substituted 10-alkyl-10H-phenothiazines were aminated using catalytic amount (5 mol %) of Cu 2 O, aqueous ammonia (NH 3 /H 2 O) solution and N-methyl-2-pyrrolidinone (NMP), the resulting mixture was then heated in a microwave oven at 120 • C for 2 h furnishing the target compounds in low to excellent yields, Scheme 76.…”
Section: Miscellaneous Synthesismentioning
confidence: 99%